Personal finance - Sunsuwa, Bala A. (Jos, Nigeria : Confidence Concepts, 2014)
A guide on how to manage personal resources from simple practices of budgeting and saving to the complex field of investment. It provides accurate information and knowledge on investing in various areas - common stocks, bonds, commodities, real estate, and insurance schemes.The book also exposes how to choose between alternative investment tools, retirement planning and plans, and manageing personal debt.
Includes bibliographical references and index.
oif 23/10/14
Loans
Keywords: Finance, Personal; Investments